Taxonomic and synonymic world catalogue of the Charipinae and notes about this subfamily (Hymenoptera: Cynipoidea: Figitidae) - Ferrer-Suay, Mar; Paretas-Martínez, Jordi; Selfa, Jesús; Pujade-Villar, Juli (Zootaxa, 2012)
The Charipinae (Cynipoidea: Figitidae) are a small group of Hymenoptera biologically characterized as being secondary parasitoids of aphids and psyllids (Hemiptera) (Menke & Evenhuis, 1991). A total of 281 species of Charipinae have been described since the first species was described by Westwood (1833) (including two fossils, one of them recently transferred in a new family, Protimaspidae). An updated world catalogue of the Charipinae is presented here, with 168 valid species: 111 included in Alloxysta Förster, 31 in Phaenoglyphis Förster, 13 in Dilyta Förster, 5 in Apocharips Fergusson, 4 in Thoreauana Girault, and 1 in Dilapothor Paretas-Martínez & Pujade-Villar, Lobopterocharips Paretas-Martínez & Pujade-Villar, Lytoxysta Kieffer and †Protocharips Kovalev. Eight species are considered as nomen nudum: Allotria fusca Dahlbom, 1842; Allotria thoreyi Dahlbom, 1842; Xystus xanthocephala Dahlbom, 1842; Allotria pusillina Giraud, 1877; Charips aphidiinaecida de Santis, 1937; Alloxysta keudelli Hedicke, 1927; Allotria amygdali Buckton, 1879 and Allotria polita Provancher, 1881. Six as nomen dubium: Allotria (Allotria) recticornis atra Kieffer, 1902; Allotria (Allotria) brevicornis Kieffer, 1902; Allotria (Allotria) orthocera Kieffer, 1902; Xystus femoralis Hartig, 1841; Charipsella laevigata Brèthes, 1913; Dilyta (Alloxysta) ignorata Kieffer, 1900. Three species are incertae sedis: Charips silvicola Belizin, 1928, Cynips atriceps Buckton, 1879 and Allotria (Allotria) testaceipes Kieffer, 1902. Two species are here synonymized: Alloxysta discreta (Förster, 1869) with A. ramulifera (Thomson, 1862) and A. megaptera (Cameron, 1889) with A. ruficollis (Cameron, 1883). Two species are raised from synonymy and considered here as valid species: Alloxysta cameroni (Cameron, 1883) and A. marshalliana (Kieffer, 1900). New names for species of Alloxysta are presented for homonimies with other Alloxysta species derived from the new combinations: Alloxysta ionescui Pujade-Villar & Ferrer-Suay new name for Alloxysta luteipes (Ionescu, 1969) n. comb., Alloxysta forshagei Pujade-Villar & Ferrer-Suay new name for Alloxysta bicolor (Ionescu, 1959) n. comb., and Alloxysta mattiasi Pujade-Villar & Ferrer-Suay new name for Alloxysta luteipes (Ionescu, 1959) n. comb. Also a new name to Phaenoglyphis is presented for the same reason before mentioned but without new combination: Phaenoglyphis hedickei Pujade-Villar & Ferrer-Suay new name for Phaenoglyphis longicornis Hedicke, 1928 and two new combinations are presented: Alloxysta rufa (Ionescu, 1959) n. comb and Alloxysta consobrina (Zetterstedt, 1838) Forshage n. comb. This catalogue includes: (i) a diagnosis of the subfamily with the most important taxonomic characters for species recognition, and illustrations of these characters; (ii) a key to genera; (iii) a list of all authors describing species of Charipinae; and (iv) a host table. The distribution of the Charipinae includes 106 Palaearctic species, 37 Nearctic, 11 Neotropical, 10 Afrotropical, 7 Oriental and 11 Australian. The species Alloxysta victrix (Westwood, 1833), A. fuscicornis (Hartig, 1841) and Phaenoglyphis villosa (Hartig, 1841) are cosmopolitan.